2014
DOI: 10.1002/2014gl060239
|View full text |Cite
|
Sign up to set email alerts
|

Response of the high‐resolution Chinese loess grain size record to the 50°N integrated winter insolation during the last 500,000 years

Abstract: The global ice volume change regulates the Earth's climate and has been characterized by 100,000 year cycles over the last 700,000 years. The Asian inland winter climate change is proposed to show primary 100,000 year cycles that mimic ice volume changes. Here we calibrate the age of a high-resolution grain size record over the last 500,000 years with a grain size age model. The results show a primary 41,000 year cycle and a weaker 100,000 year cycle during the last~500,000 years. We suggest that the primary 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
1
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 38 publications
(89 reference statements)
2
1
0
Order By: Relevance
“…1a) on the central CLP. A similar result was obtained at the Lanzhou (LZ) loess section on the western CLP by Chen et al (2014), who found that the S4 paleosol is the best-developed soil of the past 1.4 Ma and has higher MS values than the S5 unit. In particular, Holly pollen (Ilex sp.)…”
supporting
confidence: 79%
See 1 more Smart Citation
“…1a) on the central CLP. A similar result was obtained at the Lanzhou (LZ) loess section on the western CLP by Chen et al (2014), who found that the S4 paleosol is the best-developed soil of the past 1.4 Ma and has higher MS values than the S5 unit. In particular, Holly pollen (Ilex sp.)…”
supporting
confidence: 79%
“…In contrast, S4 is the most highly developed paleosol (Sun et al, 2006;Shi et al, 2012Shi et al, , 2013. The same phenomenon reported in the LZ loess section (Chen and Zhang, 1993;Chen et al, 2014) matched well with the JY loess section, indicating the MIS 11 may be the warmest intervals of the past 650 ka on the western CLP. If the S4 paleosol in the JY section genuinely represents the warmest interglacial of the past 650 ka, then it should be reflected in those properties that are associated with the intensity of pedogenesis (e.g.…”
Section: S4 Represents a Relative Warmer And Drier Episode Of The Past 650 Ka On The Western Clpsupporting
confidence: 54%
“…In contrast to the plethora of magnetoclimatological data from the hinterland of the CLP, there is a dearth of systematic magnetoclimatological investigations of the weakly weathered loesspaleosol couplets developed in the semi-arid western CLP. Here, the strong East Asian winter monsoon resulted in rapid accumulation of loess, yielding thick loess profiles (Burbank and Li, 1985;Ding et al, 1990;Jahn et al, 2001;Sun et al, 2006;Deng, 2008;Chen et al, 2014;Wang et al, 2014). However, weak pedogenesis due to limited monsoon precipitation has limited the application of magnetic parameters, especially those that are sensitive to the East Asian summer monsoon (e.g., magnetic susceptibility).…”
Section: Introductionmentioning
confidence: 99%